Bostadsgård på bjälklag : en omgestaltning av kvarteret Trumman i Malmö - Nilsson, Matilda (SLU/Dept. of Urban and Rural Development, 2011)
This essay discusses joist floor, and the land-building at these structures. In Malmoe there is a neighborhood called Trumman that has a courtyard where an underground garage is located. What possibilities are there in this place and how would an alternative design look? These issues will this essay answer. In the result part it is both described how the joist in Trumman looks and how it is built correctly. In order to provide an alternative design, I investigated the specific features of the site. The features I came to know about due to an interview with the landscape architect who made the current design, contact with the person in charge of land-building and through inventory and analysis. The analysis method that I used was the SWOT, which looks at a place's strengths, weaknesses, opportunities and threats. The current design is open and exposed. With my redesign of the courtyard would make it more of use and a place where residents want to stay. From my interview with the landscape architect I relies in my discussion that the joists is not the most limiting condition at design. But there are other wills which would like to take part of the process that are important to take in to consideration.